2017
DOI: 10.1007/s00248-017-1109-5
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Microbiota of Tadpoles Differs from Those of Syntopic Aquatic Invertebrates

Abstract: Bacterial communities associated to eukaryotes play important roles in the physiology, development, and health of their hosts. Here, we examine the intestinal microbiota in tadpoles and aquatic invertebrates (insects and gastropods) to better understand the degree of specialization in the tadpole microbiotas. Samples were collected at the same time in one pond, and the V4 region of the bacterial 16S rRNA gene was sequenced with Illumina amplicon sequencing. We found that bacterial richness and diversity were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Similarly, a study focused on non-human primates found that host phylogeny had a larger impact than dietary niche on gut microbiomes [33]. This finding is also supported by studies in other taxa including larval amphibians and aquatic invertebrates [71]. Previous studies found a more prominent role of host diet in shaping the gut microbiome [72,73], particularly within clades such as lizards [74], fish [32,67,75], birds [76,77], or mammals [78].…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, a study focused on non-human primates found that host phylogeny had a larger impact than dietary niche on gut microbiomes [33]. This finding is also supported by studies in other taxa including larval amphibians and aquatic invertebrates [71]. Previous studies found a more prominent role of host diet in shaping the gut microbiome [72,73], particularly within clades such as lizards [74], fish [32,67,75], birds [76,77], or mammals [78].…”
Section: Discussionmentioning
confidence: 66%
“…The microbiome of tadpoles from this study is slightly different than previous studies. Proteobacteria and Firmicutes dominated in other studies [31,[64][65][66] but here we found that Fusobacteria were also important. Alpha and phylogenetic diversity were also mostly higher in our study than in previous ones [31,[64][65][66].…”
Section: Discussionsupporting
confidence: 66%
“…Proteobacteria and Firmicutes dominated in other studies [31,[64][65][66] but here we found that Fusobacteria were also important. Alpha and phylogenetic diversity were also mostly higher in our study than in previous ones [31,[64][65][66]. The knowledge about the gut microbiome of tadpoles is still limited to a few species and quantitative comparisons of diversity across studies is problematic because of differences in sampling procedures, sample processing, data cleaning, and the algorithms and databases.…”
Section: Discussionsupporting
confidence: 66%
“…1b) in this study. In another study, the composition and abundance of intestinal microbiota was found to be quite different in aquatic invertebrates collected from a single small pond [33]. These results suggested that certain microorganisms derived from the environment might be selectively colonized and established in the gut of the host.…”
Section: Discussionmentioning
confidence: 99%